Web of Things - Automatic Publishing and Configuration of Devices - Andrade Jr., Nailton Vieira de; Bastos, Daniel Borges; Prazeres, Cássio Vinicius Serafim (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2014: Proceedings of the 20th Brazilian Symposium on Multimedia and the Web, 2014)
The Web of Things proposes to make devices available by using Web standards and protocols. Several different devices, which can be connected to the Web of Things, demand efforts to implement specific services to deploy each of such devices. For that reason, this paper presents an approach to automatically publish and configure devices as Web of Things resources. Our approach presents models that implement device functionalities and uses such models to automatically generate Web Services for devices. This paper also presents: i) dynamic discovery and configuration of devices when connecting to a local network by using Zeroconf protocol; ii) automatic generation of applications for publishing devices on the Web of Things.